Stock discrimination of Chelidonichthys obscurus (Triglidae) in the central Mediterranean Sea using morphometric analysis and parasite markers. (2020) - Boudaya, L.; Feki, M.; Mosbahi, N.; Neifar, L.
Abstract: Assessing fish stocks has important implications for fisheries management and conservation biology. Gurnards are marine demersal fish that commonly occur in the Mediterranean, but their population in this region remains to be quantified. This study examines the population structure of the longfin gurnard Chelidonichthys obscurus (Walbaum, 1792) in waters off eastern Tunisia, using morphometry and parasite assemblages. A total of 134 fish are investigated from two studied zones – the Gulf of Hammamet and the Gulf of Gabès. Discriminant analysis is used to compare gurnard populations in the two studied zones using 13 morphometric characters and the infection parameters of seven parasites. Morphometric analysis reveals strong spatial variations between the studied zones, providing evidence for the existence of an ecological differentiation along the eastern Tunisian coast. Mahalanobis distances show that body height, pectoral fin length and first dorsal fin length are the most salient morphometric characters for determining the position of samples from the Gulf of Gabès. The effectiveness of using parasites to study longfin gurnard stocks is uncertain. The use of short-lived parasites as biological tags is questionable, at least in the present case. Future research, based on complementary approaches such as otolith microchemistry and genetics, may improve our understanding of the global stock structure of longfin gurnard to suitably inform regional organizations involved in fisheries management.